Determining the Minimum Inhibitory Concentration of Medium Chain Fatty Acids for Generic Escherichia coli, Enterotoxigenic Escherichia coli, Salmonella Typhimurium, and Campylobacter coli - R. A. Cochrane; R. G. Amachawadi; S. E. Remfry; A. B. Lerner; T. G. Nagaraja; J. C. Woodworth; S. S. Dritz; M. D. Tokach; M. C. Niederwerder; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2018)
Research has demonstrated that medium chain fatty acids (MCFA) can serve as reduction strategies for bacterial and viral pathogens in animal feed and ingredients. However, it is unknown how the type or level of MCFA impact bacteria growth. This can be tested through a minimum inhibitory concentration (MIC) benchtop assay, which identifies the lowest concentration of a chemical that prevents visible growth of a bacterium. The objective of this study was to 1) determine the MCFA MIC of C6:0, C8:0, C10:0, and C12:0 for genericEscherichiacoli, EnterotoxigenicEscherichia coli,SalmonellaTyphimurium,Campylobactercoli, andClostridium perfringens; 2) determine the MIC of commercial based MCFA products against the same bacteria; and 3) determine the effect of 2 commercial based MCFA products on the quantification of EnterotoxigenicEscherichia coli. For Exp. 1 and 2, MIC were determined by modified microbroth dilution method using a 96 well microtiter plate with a concentration of 105 CFU/mL for each bacterial strain. For Exp. 3, the two products selected for quantification were mixed with a complete swine diet and inoculated with two concentrations (106 or 102 CFU/g of feed) of aNalRstrain of EnterotoxigenicEscherichia coli(ETEC) for bacterial enumeration. From Exp. 1, the MIC of MCFA varied among bacteria species. The lowest MIC of the MCFA was 0.43% of a 1:1:1 blend of C6:0, C8:0, and C10:0 forCampylobacter coli, 0.25% C12:0 forClostridium perfringens, 0.60% 1:1:1 blend for genericEscherichia coli, 0.53% C6:0 for ETEC, and 0.40% C6:0 forSalmonellaTyphimurium. In Exp. 2, products containing high concentrations of C6:0 or C8:0 had lower MIC in gram negative bacteria. In Exp. 3, feed containing either of the commercial based MCFA products reduced (linear,P<0.05) quantifiable ETEC. Overall, the inhibitory efficacy of MCFA varies among bacteria species. This suggests that MCFA mixtures may provide a wider spectrum of bacterial control. As commercial products containing MCFA become available for livestock, it is important to consider the interaction between MCFA chain length and concentration on the potential to effectively mitigate various feed-based bacteria.
Keywords: Medium chain fatty acids; minimum inhibitory concentration; bacteria